2022
DOI: 10.1097/acm.0000000000004242
|View full text |Cite
|
Sign up to set email alerts
|

Entrustment Decision Making in the Core Entrustable Professional Activities: Results of a Multi-Institutional Study

Abstract: Purpose In 2014, the Association of American Medical Colleges defined 13 Core Entrustable Professional Activities (EPAs) that all graduating students should be ready to do with indirect supervision upon entering residency and commissioned a 10-school, 5-year pilot to test implementing the Core EPAs framework. In 2019, pilot schools convened trained entrustment groups (TEGs) to review assessment data and render theoretical summative entrustment decisions for class of 2019 graduates. Results were exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 31 publications
0
22
1
Order By: Relevance
“…The entrustment workgroup of the pilot used an iterative process of discussions, data collection, and reflection to describe principles, plans, and activities related to the entrustment process; choices schools made about the entrustment process, why choices were made, and challenges with the entrustment process; data considered for each EPA; and results of entrustment decision-making for the first graduating cohort …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The entrustment workgroup of the pilot used an iterative process of discussions, data collection, and reflection to describe principles, plans, and activities related to the entrustment process; choices schools made about the entrustment process, why choices were made, and challenges with the entrustment process; data considered for each EPA; and results of entrustment decision-making for the first graduating cohort …”
Section: Methodsmentioning
confidence: 99%
“…Implementing a centralized entrustment process at a medical school involves a major curricular change and poses a variety of cultural, logistical, analytic, psychometric, and ethical challenges . Evaluation of entrustment decision-making for the 2019 graduating cohort highlighted multifactorial challenges in assessment of some of these activities in the workplace, suggesting the need to consider curriculum content revisions and increase availability of WBAs and other assessment data.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… 2 , 42 Despite limitations of self-assessment data, we do note that studies have shown similarities in patterns across various EPAs—to patterns we observed across EPAs in self-assessed skills in both high SAA and moderate SAA groups—in assessments by others of students’ readiness to perform EPAs under indirect supervision. 32 , 42 , 43 …”
Section: Discussionmentioning
confidence: 99%